The Impact of Functional Status to the Risk of Depression in Elderly with Hypertension - Hijriana, Isni; Ismail, Ismail; Mardhiah, Ainal (Indonesian Journal of Global Health Research, 2024)
Decreased function that occurs in the elderly is usually related to the disease and its severity, but in the end these various factors will affect the functional abilities and well-being of an elderly person. The purpose of this study was to determine the predictor functional status on the risk of depression in elderly people with hypertension in the Keumala Health Center Work Area. Method: This research is analytic in nature with a cross-sectional study design. The population in this study were all elderly people who suffer from hypertension and are over 60 years old in the working area of the Keumala Health Center, totaling 104 elderly people and the samples in this study were 51 elderly people. The sampling technique is purposive sampling. Data was collected using a questionnaire. Results: the univariate test found that the functional status of the elderly with hypertension was mostly in the partially dependen category, namely 41 respondents (80.4%), the risk of depression in the elderly with hypertension, the majority were in the moderate category, namely 39 respondents (76.5%). The results of the bivariate test showed that there was a relationship between functional status and the risk of depression in the elderly with hypertension at the Keumala Health Center, Pidie Regency (P=0.000). Elderly families can help and accompany patients in improving their functional status so that patients can carry out their daily activities independently so that they can reduce their depression.